PERANCANGAN DAN PENGEMBANGAN SISTEM INFORMASI PADA TOKO BUNGA AMAI DI DILI TIMOR LESTE BERBASIS WEB - Freitas, Tomas Antonio Correia; Widyastuti, Naniek; Iswahyudi, Catur (Jurnal Script, 2014)
ABSTRACTComputer technology is one technology that is widely used in activities everyday. An information systems often use computers to process data useful information for world of education, offices, industry, business, entertainment, military, tourism, and the others. E-commerce is a web-based online trading applications with the Internet media. During this time many buyers of conventional trade. Where the demands of the buyers to come and interact directly to the seller. Software technology used indevelopment are PHP and MySQL database support with the language javascript, jquery with this application is expected to make it easy for buyers to choose and order the products that are sold in Amai stores, and can be utilized to improve the performance Amai Store. The purpose of the study of the making of this final project is to create an e-commerce application that has high user interaction with the use of features according to standard. E-commerce user experience. This application is expected to provide comfort and convenience of visitors in the shop and take advantage of existing features.Keywords: E-commerce, Flower Online Sales, PHP, JavaScript, and MySQL.